DEVELOPMENT OF SHOT TECHNOLOGY USING BY-PRODUCTS OF JUICE PRODUCTION - Lapytska Надія; Biloborodko Анастасія (Biota. Human. Technology, 2024)
The paper considers the possibility of using extracts from wild berries for the production of tinctures that will be used in the recipe of shots. The relevance of expanding the range of drinks in bars and restaurants has been established. It has been proven that the use of by-products of juice production - juice extracts - will be profitable, since restaurants often order fresh juices, the production of which accumulates a significant number of by-products. In addition, squeezes are accumulated to a large extent at juice plants, which will reduce the risks of a shortage of raw materials. In the presented work, the ingredients for the production of shots are selected. Attention has been drawn to reducing the alcohol content in this drink and increasing its functionality. Cranberry and sea buckthorn extracts were used to prepare tinctures. Vodka was used as an extractant. The ratio of squeeze: vodka was 1: 5. Extraction was carried out at a temperature of 8...10 °C for 12...24 hours. After that, the tincture was stirred and filtered. The filtrate was used to prepare shots. In order to develop the formulation of the new shot, the quality indicators of the raw materials that will be used for its production were studied. It was established that tinctures made from cranberry and sea buckthorn extracts have 44.4 and 56.0 % lower strength compared to vodka. Along with the fact that orange juice and pineapple syrup, which do not contain alcohol at all, will be used for the production of shots, it can be argued that the goal of creating an alcoholic beverage for restaurants with a reduced alcohol content and increased functionality has been achieved. Shots are layered drinks. In order to obtain “layering”, one should clearly understand the density of the raw material that will be used. According to research data, pineapple syrup has the highest density, vodka the lowest. According to the data obtained in the work, a recipe and technological scheme for the production of shots using by-products of juice production was developed. The obtained drinks were characterized by high organoleptic indicators, had an attractive appearance and an original aroma. The purpose of the article is to develop the technology of shots for the use of sea buckthorn and cranberry extracts. Methodology. Physico-chemical and organoleptic research methods were used during the work. Processing of the results was carried out using «MC Excel databases». The scientific novelty is that the complex processing of raw materials is proposed in order to increase the profitability of the production of drinks and give them functionality due to the use of sea buckthorn and cranberry extracts in the production of shots in restaurants. Conclusions: the expediency of using tinctures from extracts of wild berries, cranberries and sea buckthorn in the production of mixed drinks has been proven. Selected ingredients that allow you to get an original high-quality shot. The technology of obtaining shots for the use of tinctures from cranberry or sea buckthorn extracts has been developed. The organoleptic parameters of the obtained drinks were analyzed. Further research at work is formulated.